Wisława Szymborska w roli redaktora "Poczty literackiej". Obraz nadawcy = Wisława Szymborska as an editor of "Literary Post" ["Poczta literacka"] columns. The view of the addresser - Wojciechowska, Anna (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The aim of the paper is to examine Wisława Szymborska's texts published in a weekly "Literary Life" ["Życie Literackie"]. From 1960 to 1968 a future Nobel Prize in Literature Laureate was a co-editor of a column called "Literary Post". Szymborska evaluated readers' literary attempts sent in the letters to the editor. She replied to the letters anonymously, by means of a polysemic form "we". The analysis of the ways the speaker's presence is revealed in the texts helps to reconstruct the view of the addresser. The empirical part of the paper is preceded with a short description of the column in question as well as the press genre under study.
Keywords: Szymborska, Wisława (1923-2012); "Życie Literackie" (czasopismo); nadawca; addresser